Enhancing Technical Vocabulary Through Morphological Analysis Instruction For Biology-majored Students - Kent-David Juen; Nhon Dang (TTU Review, 2021)
This paper aims to investigate the effectiveness of morphological analysis instruction on gradetenbiology-major studentsin TanTaoHigh SchoolfortheGifted inLong An, Vietnam, andto ﬁnd out whether they can catch up with the level of biotechnology students in Tan Tao University, in terms of science vocabulary performance. The instruction selectively targeted technical multisyllabic words that occur frequently in the participants’ corpus. Thirty-one students including eighteen grade-ten biology students as the experimental group and thirteen biotechnology students as the control group participated in the study. For data collection, pre-posttest was designed, validated and applied for the experimental and control group. Apart from the regular teaching method, the experimental group also received explicit morphemic analysis instruction, while the control group only received their regular teaching. Pretest to posttest results revealed that each group registered an increase in the respective means, however, the experimental group surpassed the control group up to 5.9 mean difference. Morphemic analysis conﬁrms its effectiveness in boosting the students’ vocabulary acquisition of multisyllabic terminologies that facilitates their learning. The paper ended with some pedagogical implications for teaching technical terms.